PERBANDINGAN NILAI STABILITAS DAN FLOW CAMPURAN AC-WC PADA PENGUJIAN MARSHALL MENGGUNAKAN ALAT UJI DIGITAL DAN ANALOG - Zulfikar, Grandis; Sulistyono, Sonya; Hayati, Nunung Nuring (FSTPT Indonesia, 2015)
Test characteristics of Marshall stability and flow generating value. Marshall test can use two types of tools, test equipment digital and analog test equipment. Digital test equipment in use and reading of data using a computer system. While analog test equipment in use and reading of data processing manually. This study used a mixture of AC-WC with optimum bitumen content of 6.5% were obtained from the results of the preliminary test, then made 28 test specimens (2 x 14). Marshall testing were performed using the Marshall test equipment. This study was guided by the Indonesian National Standard (SNI) preformance testing materials, mixing aggregate with asphalt, and the Marshall test. Based on the results of volumetric analysis and testing of Marshall characteristic analysis showed an average difference of two of the digital and analog test equipment there is no real difference. The average value of the results of the analysis and testing of the Marshall characteristics using a digital test equipment was obtained: density (kg / m 3) = 23,6; VMA (%) = 18,69; VIM (%) = 4,80; VFA (%) = 74,37; stability (kg) = 2165,00; flow (mm) = 4,11; MQ (kg / mm) = 574,48. Analog test equipment is obtained:: density (kg / m 3) = 23,6; VMA (%) = 18,76; VIM (%) = 4,88; VFA (%) = 74,01; stability (kg) = 2000,67; flow (mm) = 3,60; MQ (kg / mm) = 585,73.